Recent Advances in Dual‐Atom Site Catalysts for Efficient Oxygen and Carbon Dioxide Electrocatalysis. Issue 7 (23rd May 2022) - An, Qizheng; Jiang, Jingjing; Cheng, Weiren; Su, Hui; Jiang, Yong; Liu, Qinghua
Abstract: Atomically dispersed metal catalysts have been widely used in electrocatalysis because of their outstanding catalytic activity and high atomic utilization efficiency. As an extension of single‐atom catalysts (SACs), dual‐atom catalysts (DACs) provide new insights for the development of atomic‐scale catalysts. Higher metal loading and more flexible active sites endow DACs with improved catalytic performance as well as optimized reaction mechanism model. In this review, DACs are firstly classified according to their configurations and metal sites. Subsequently, the synthetic strategies and characterization techniques of DACs are introduced. Furthermore, the applications of DACs are exemplified in various electrocatalytic reactions, including oxygen reduction reaction, oxygen evolution reaction and carbon dioxide reduction reaction. Finally, the prospects to be expected and challenges to be faced with are discussed. Abstract : This review classifies the dual‐atom catalysts (DACs), introduces the synthetic strategies and characterization techniques of DACs, exemplifies the applications of DACs in various electrocatalytic reactions, and finally discusses the prospects and challenges to be faced with for DACs.